Frequency of Religious Tourist Visits Based on Education Level and Occupation (Case Study at the Tomb of Sheikh Maulana Syamsuddin, Pemalang) - Susdarwono, Endro Tri (CV. Austronesia Akademika, 2025)
Religious tourism has long played an important role in both spiritual life and local economic development, offering benefits for communities and visitors alike. In Indonesia, one of the prominent religious tourism sites is the tomb of Sheikh Maulana Syamsuddin in Pemalang, which attracts pilgrims from various educational and occupational backgrounds. This study aims to examine the frequency of religious tourist visits to this site based on education level and occupation. Using a quantitative descriptive approach, data were collected from 200 respondents over a four-month period (April–July) through random sampling. Questionnaires served as the primary research instrument, and data were analyzed using the contingency correlation method to determine the relationship between visit frequency and socio-demographic variables. The findings reveal a correlation between education level and the frequency of visits, with tourists holding junior and senior high school education levels dominating the “very frequent” category, while those with bachelor’s degrees were most often in the “very rare” category. Similarly, visit frequency was correlated with occupation, where entrepreneurs and private employees reported higher frequencies, while retirees and civil servants tended to visit less often. The calculated correlation coefficients were 35.23% for education level and 34.64% for occupation, indicating a weak but notable relationship between these variables and visitation patterns. These results highlight that socio-demographic factors influence participation in religious tourism, suggesting that strategies to promote sustainable religious tourism development should consider the educational and occupational characteristics of potential visitors.